Small molecule inhibition of Axl receptor tyrosine kinase potently suppresses multiple malignant properties of glioma cells - Vouri, Mikaella (Oncotarget, 2015)
Glioblastoma multiforme (GBM) often features a combination of tumour suppressor gene inactivation and multiple oncogene overactivation. The Axl receptor tyrosine kinase is found overexpressed in GBM and thought to contribute to invasiveness, chemoresistance and poor survival. Here, we have evaluated the effect of BGB324, a clinical candidate Axl-specific small molecule inhibitor, on the invasive behaviour of human GBM cells in vitro, as an indicator of its potential in GBM therapy and also to elucidate the role of Axl in GBM pathogenesis. Two cultured adult GBM cell lines, SNB-19 and UP007, were treated with Gas6 and/or BGB324, and analysed in assays for survival, 3D colony growth, motility, migration and invasion. Western blot was used to detect protein expression and signal protein phosphorylation. In both cell lines, BGB324 inhibited specifically phosphorylation of Axl as well as Akt kinase further downstream. BGB324 also inhibited survival and proliferation of both cell lines in a concentration-dependent manner, as well as completely suppressing migration and invasion. Furthermore, our results indicate co-operative activation between the Axl and Tyro3 receptors, as well as ligand-independent Axl signalling, to take place in GBM cells. In conclusion, small molecule inhibitor-led targeting of Axl may be a promising therapy for GBM progression.